Analisis Asosiasi Kultural atas Warna - Mita Purbasari; Laura Christina Luzar; Yusaira Farhia (Humaniora, 2014)
Cultural association analysis of color is an approach to know color from the side of culture. Unlike the previous color studies which see the color from the aspect of psychology, this research of color aims to provide insight based on the colors from local culture. Johannes Itten’s theory of color was used as a basis of thought in this research. The theory was reflected to Indonesian cultures, and this time, represented by Java island. Research used qualitative method by literature study, interviewing the color experts, historians and artists, visiting cultural centers. Results of the research are in the form of morphological matrix cultural over color. Matrix of analysis resulted in argument and study proposal. Students implemented the color schemes from 5 big cities in Java. They were asked to change the color composition of food and beverage packaging. Students may use, explore, and maximize the principle of color in visual communication to achieve contrast and balance.